Study of nutritional status, comorbidities and other risk factors associated with dengue fever: data from a tertiary hospital in North India - Kaur, Harharpreet; Kaur, Harpreet; Kaur, Navjot; Kaur, Kawalinder (International Journal of Advances in Medicine, 2017)
Background: Dengue is a major health problem in India. The understanding of the factors which predispose to the infection and which are involved in its progression is fundamental for improved clinical outcomes. This study was initiated with the aim of identifying the patient population at risk and comorbidities involved in the development of complications. Methods: This was an observational and case control study in which 130 cases and controls taken from the healthy population were evaluated with respect to data regarding demographics, complications and co morbid metabolic diseases. Results: There was a predominance of males in cases as compared to controls especially between ages of 21-30 years . There was a significantly higher rate of comorbidities in cases as compared to controls and constituted 62.3% of the total cases. Obese /overweight cases were 60.8 %, fatty liver -30.76%, diabetics- 15.4 %, hypertensives 15.4%, cases of hypothyroidism 2.3 %, renal diseases 5.38% and ischemic heart disease 6.92%, 18.50% cases developed complications and severe disease (SD). There was a significant association of pleural effusion/ascites and gall bladder edema with SD. Association of comorbidities with SD was however not significant. Such cases tended to develop complications like heart failure, angina, renal failure and multiorgan failure and were difficult to treat. 5 (3.84%) patients died. 4 had associated comorbidities. Conclusions: Comorbidities like obesity predispose to dengue infection and are liable to cause serious complications knowledge of which can prompt early clinical intervention and reduction of mortality.